A highly selective and sensitive fluorescence probe for rapid detection of hypochlorite in tap water and cancer cells. Issue 107 (7th November 2016) - Pang, Lanfang; Zhou, Yanmei; Gao, Wenli; Song, Haohan; Wang, Xiao; Wang, Yong
Abstract : A fluorescence probe for the rapid detection of hypochlorite in tap water and cancer cells. Abstract : The 7-hydroxy-4-methylcoumarin as an "off–on" fluorescent probe exhibited excellent selectivity and sensitivity towards hypochlorite over other reactive oxygen species and relevant ions. Upon treatment with hypochlorite, the fluorescence intensity of the probe gradually increased 86-fold. A good linear increase of the fluorescence intensity could be observed with increasing hypochlorite concentration over a wide linear range of 0–150 μM, and a detection limit as low as 67 nM was obtained. Moreover, the probe could also be successfully applied for the detection of hypochlorite in tap water and living cells, which provided great potential for the quantitative detection of hypochlorite in water samples and cancer cells.